2015
DOI: 10.1002/ajmg.a.37347
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 10q22.3–q23.3 encompassing BMPR1A and NGR3 associated with congenital heart disease, microcephaly, and mild intellectual disability

Abstract: Chromosome region 10q22.3-q23.3 contains several low copy repeats (LCRs) and is prone to recombination. Deletions with breakpoints within LCR3 and LCR4 have been described to be associated with intellectual disability and dysmorphic features, while the reciprocal duplications are rarely reported. We present an additional case with multiple congenital anomalies that include microcephaly, cardiac defect, and mild intellectual disability, in which a de novo interstitial 8.2-Mb duplication of 10q22.3-q23.3, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Among the top hits in the logistic regression analysis (Table 6) some could impact TB susceptibility as they are involved in immune functions. The most significant interaction was between rs2631914 (LINCO2153), which is upregulated in people with major depressive disorder (58) and rs8067702 (RTN4RL1), previously associated with congenital heart disease, microcephaly and mild intellectual disability (59). While this interaction is not very informative in the context of TB three other interactions were identified that could impact TB susceptibility ( Table 6).…”
Section: Interaction Analysismentioning
confidence: 99%
“…Among the top hits in the logistic regression analysis (Table 6) some could impact TB susceptibility as they are involved in immune functions. The most significant interaction was between rs2631914 (LINCO2153), which is upregulated in people with major depressive disorder (58) and rs8067702 (RTN4RL1), previously associated with congenital heart disease, microcephaly and mild intellectual disability (59). While this interaction is not very informative in the context of TB three other interactions were identified that could impact TB susceptibility ( Table 6).…”
Section: Interaction Analysismentioning
confidence: 99%
“…Some potential causative genes have been identified in the critical region 10q23.1q23.31. In particular, overexpression of BMPR1A and PTEN has been considered to be implicated in congenital heart disease [Crackower et al, 2002;Gaussin et al, 2002], while NGR3 , which plays an important role in early mammary morphogenesis, could contribute to limb malformation and short stature [Tang et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals harboring smaller interstitial duplications (10q22.3q23.3) are also known, presenting with microcephaly, cardiac defects, and developmental, speech, and motor delay [van Bon et al, 2011;Tang et al, 2015].…”
mentioning
confidence: 99%
“…Recurrent deletions at 10q22.3q23.3 mediated by LCR3-4 are associated with intellectual disability, developmental delay, dysmorphic features, behavior problems and other neurodevelopmental disorders, whereas reciprocal duplications are contributed to distinctive facial features, cognitive impairments, congenital heart disease, and delays in language and motor development. Interstitial deletions or duplications at 10q22.3q23.3 are infrequently reported, and a distinct clinically recognizable syndrome has not emerged [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only eight patients with de novo deletions at 10q22 have been reported, and the main clinical features include speech impairments, dysmorphic features, genital anomalies, intellectual disability and developmental delay [7,[11][12][13][14][15]. Dufke and Han each described a case with a de novo duplication at 10q22.2q22.3~23.1 and 10q22q24 detected by G-banding analysis respectively, whereas the two segments not only covered the 10q22 region but also LCR3-4 which was demonstrated to be clinically significant [8][9][10]16,17]. Here, we report two unrelated patients with de novo overlapping duplications at the 10q22 interval that are 6.4 Mb and 9.8 Mb in size separately, detected by high-resolution CMA.…”
Section: Introductionmentioning
confidence: 99%